Efektivitas Gel Anti Jerawat Ekstrak Etanol Rimpang Jahe Merah (Zingiber officinale Rosc. Var. Rubrum) terhadap Propionibacterium acnes dan Staphylococcus epidermidis - SYF. OCTY NOVY FISSY; RAFIKA SARI; LIZA PRATIWI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Acne can be caused by bacteria, such as Propionibacterium acnes and Staphylococcus epidermidis. Red ginger (Zingiber officinale Rosc. var. rubrum) has been studied for its antibacterial activity. The aims of this research was to determine the minimum inhibitory concentration of red ginger rhizome ethanol extract against P. acnes and S. epidermidis bacteria and the effectiveness when the extraxt formulated into gel. The simplicia was extracted by soxhlet using 96% ethanol. Diffusion method was used to measure the minimum inhibitory concentration (MIC) of extract. Afterwards, the extract was forrmulated into gel by using three variation of HPMC 4000 and carbopol 934 as gel base with ratio of 70:30 (Formula I), 50:50 (Formula II) and 30:70 (Formula III). Gel evaluation included organoleptic, spreadability, adhesive property, pH and antibacterial effectiveness. The data was analyzed by R-Commander program 2.14.1 Version. The results showed MIC values are 0.45% against P. acnes and 0.5% against S.epidermidis. The results of evaluation for 30 days of storage showed that the gels had stable pH and adhesion, homogenous, whereas the spreadablity of gels increased. Antibacterial evaluation showed that formula I give the best effectiveness with 16,11 mm zone of inhibition against P. acnes and 14,00 mm against S.epidermidis.